THE EFFECT OF PROMOTION THROUGH SOCIAL MEDIA (FACEBOOK) AND WORD OF MOUTH ON INTEREST IN BUYING YAMAHA AUTOMATIC MOTORCYCLES (Case Study on Yamaha Thamrin Brother Motor Lebong Consumers) - Fahmi Ramadhona; Gilang Prasetyo Hari; Islamuddin (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study aims to analyze the influence of promotion through Facebook social media and word of mouth on the purchase intention of Yamaha automatic motorcycles among consumers of Yamaha Thamrin Brother Motor in Lebong Regency. A quantitative method with a case study approach”become “a quantitative approach using a case study design” for smoother academic phrasing, in which data were collected through questionnaires distributed to 75 respondents. The classical assumption tests, including normality, multicollinearity, and heteroscedasticity, is more standard in research writing. The results of the multiple linear regression analysis revealed that both Facebook social media promotion and word of mouth had a positive and significant effect on purchase intention, with word of mouth contributing a stronger effect. The t-test results indicated that each independent variable significantly influenced the dependent variable individually, while the F-test showed that both variables simultaneously had a significant effect. The Adjusted R² value of 0.628 indicates that 62.8% of the variation in purchase intention can be explained by the two independent variables. In conclusion, digital promotion strategies and consumer-to-consumer information dissemination play a vital role in shaping consumer purchasing decisions for Yamaha automatic motorcycles